ANALYSIS ECONOMY HOUSE LADDER FARMER CORN IN SEI MENCIRIM VILLAGE, KUTALIMBARU DISTRICT, DELI SERDANG REGENCY - Yurmaini; Fuad Balatif; Aadil Hussain Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze: 1) Sources of income for corn farmers in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency, 2) Household income of corn farmers in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency, 3) Household consumption of corn farmers in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency. The study was conducted in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency from April to May 2023 with a sample of 50 farmers. The research method used was a survey method. Data analysis used were descriptive analysis, farm income analysis, and household income analysis. The results of this study indicate that sources of income for corn farmers in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency come from two sources: income from the agricultural sector or corn farming and income from outside the agricultural sector, namely as craftsmen, drivers, traders, and civil servants. Household income for corn farmers in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency is Rp. 6,250,000.00, derived from corn farming (Rp. 5,050,000.00) and from non-agricultural sources (Rp. 1,200,000.00). Household consumption is divided into two categories: food and non-food. The average household consumption in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency is IDR 6,100,000.00 per season.